RENEWABLE ENERGY POTENTIAL AND OPPORTUNITIES FOR ORGANIC FARMING IN THE REGION OF THE ŠALEK VALLEY - Špeh, Natalija; Kopušar, Nataša (Journal of Energy Technology, 2024)
The purpose of this research paper is to examine the rural area of the Šalek Valley and to determine what the potential for the promotion of organic farming is in an area that is traditionally better known as an electricity producer and industry supplier. The predominant agricultural activity is livestock, and there is almost no market-oriented horticulture. The farms included in the study were from three neighbouring municipalities: Velenje, Šoštanj and Šmartno ob Paki; 1218 farm owners were invited to participate, and the research was presented orally to 370 farmers. Only 40 surveys were returned and completed; nine of these were declared to be organic farms and four to farms in conversion. The average age of the surveyed farm owners was over 50 years and was not significantly different regarding the farms’ orientation; 63% of family farms have already planned for a successor, less so with the organic agricultural holdings. Since organic farms also showed livestock to be the predominant agricultural activity, a good potential for the renewable (biomass) energy production, e.g. co-generation of electricity and heat, was assumed. As we were interested in the economic prospects of the farms, we wanted to know their attitude to energy supply as a supplementary farm activity or whether they had had any experience with renewable energy sources. With these input data, we want to check: a) agricultural holdings, especially those that were organic-oriented, which are expected to have the prominent role in the future food supply; b) how the owners plan the on-farm activities; and c) the current energy supply and openness of farmers to using other energy sources.